Negocios y Gestión en Antioquia. La trayectoria empresarial de don Alejandro Echavarría Isaza (1859-1928) (2019)
This paper studies the entrepreneurial path of the "antioqueño" Alejandro Echavarra Isaza from his birth, in the mid nineteenth century, until his death in 1928. Its central axis deals with the diversity of his different businesses and with the way in which family issues were related to them and to his financial and economic behavior. The diversification of his investments, the innovation, and the creation of new firms, suggest that he was a true entrepreneur in the Schumpeterian sense of this term.